Dissent and denunciation in ebi yeibo's the fourth masquerade (2016)
One of the socio-political conditions affecting the African society right from the twilight of the twentieth century is the overwhelming widespread of terrorism. Nigeria too has been on the front page of world news due to the irascible activities of the notorious sect called Boko Haram. This research therefore investigates how Ebi Yeibo, a contemporary Nigerian poet, in his collection The Fourth Masquerade, has portrayed and reacted to the nefarious ordeals of this sect. The theoretical framework intended for the analysis of this collection a sub-tenet of postcolonialism, which is colonial mentality. While the proponents of this critical perspective argue that a homogenous group of people often associate themselves with foreign ways, this paper examines the anti-colonial mentality attributes that the Boko Haram sect claims to promote to the world as one of its key creeds, arguing that the sect exhibits principle of colonialism, such as control, power, and so on. An overview of the different perspectives of the poet's portrayal of the Boko Haram sect will certainly be the thrust of this research. Attention will be paid to the dissent and denunciative voice of the poet expressed in viciously stem tone through which the poet questions, ridicules and eventually castigates the very identity of the sect.